2022
DOI: 10.3390/ijfs11010009
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Factors of FinTech: Evidence from an Emerging Economy Country-Wide Representative Sample

Abstract: Adoption factors of Financial Technology (Fintech) services have been the subject of investigation in a growing body of extant literature. Macro-level as well as user-specific factors that contribute to the adoption of customer-facing fintech services have been studied. Emerging market studies mostly considered targeted demographic and socio-economic segments, limiting their ability to reflect a wide spectrum of relevant factors. We conducted a nationwide representative survey of 1282 individuals in Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Findings show that complexity has a negative influence on the adoption of FinTech adoption. This finding is consistent with previous studies, which also found that complexity negatively influences the adoption of FinTech (Anouze and Alamro, 2019; Hwang and Kim, 2018; Mahmud et al ., 2022). This finding suggests that FinTech services should be easy to use to attract more people to adopt them.…”
Section: Discussionsupporting
confidence: 93%
“…Findings show that complexity has a negative influence on the adoption of FinTech adoption. This finding is consistent with previous studies, which also found that complexity negatively influences the adoption of FinTech (Anouze and Alamro, 2019; Hwang and Kim, 2018; Mahmud et al ., 2022). This finding suggests that FinTech services should be easy to use to attract more people to adopt them.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, according to the UTAUT2 model, sociodemographic variables such as age, income and experience have been hypothesised to moderate the effect of fintech on behavioural intention [ 20 ]. Mahmud et al [ 37 ] found that the Fintech adoption rate was higher among the young and males, meaning that the number of females accessing fintech services was lower than that of males, thus indicating a gender gap.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Scholars have attempted to analyze this behavior from multiple angles, including Ajzen's (1991) theory of planned behavior (TPB). Khanal Mahmud et al 2023). This study used three behavioral factors to investigate customers' behavioral effects on access to and usage of FinTech services:…”
Section: Independent Variablesmentioning
confidence: 99%
“…for example, used TPB to investigate the impact of behavioral intention, attitude toward behavior, and perceived behavior on customer satisfaction. Other researchers have combined trust with other variables to re ect customers' behavior toward technology applications, digital payments, and FinTech services(Hassan et al 2023;Kurniasari et al 2022;Nathan et al 2022;Mahmud et al 2023…”
mentioning
confidence: 99%